TASL Practice Guidance on the Clinical Assessment and Management of Patients with Nonalcoholic Fatty Liver Disease - Yilmaz, Yusuf; Zeybel, Mujdat; Adali, Gupse; Cosar, Arif Mansur; Sertesen, Elif; Gokcan, Hale; Idilman, Ramazan (Kare Publ, 2023)
Nonalcoholic fatty liver disease (NAFLD) is a multisystem disease and is significantly associated with obesity, insulin resistance, type 2 diabetes mellitus, metabolic syndrome, and cardiovascular disease. NAFLD has become the most prevalent chronic liver disease in Western countries, and the proportion of NAFLD-related cirrhosis among patients on liver transplantation waiting lists has increased. In light of the accumulated data about NAFLD, and to provide a common approach with multi-disciplines dealing with the subject, it has become necessary to create new guidance for diagnosing and treating NAFLD. This guidance was prepared following an interdisciplinary study under the leadership of the Turkish Association for the Study of the Liver (TASL), Fatty Liver Special Interest Group. This new TASL Guidance is a practical application guide on NAFLD and was prepared to standardize the clinical approach to diagnosing and treating NAFLD patients. This guidance reflects many advances in the field of NAFLD. The proposals in this guidance are meant to aid decision-making in clinical practice. The guidance is primarily intended for gastroenterology, endocrinology, metabolism diseases, cardiology, internal medicine, pediatric specialists, and family medicine specialists.
Keywords: Nonalcoholic fatty liver disease; nonalcoholic steatohepatitis; hepatosteatosis; noninvasive diagnostic tests; chronic hepatitis; cirrhosis